Microbiota-gut-brain axis pathogenesis and targeted therapeutics in sleep disorders - Pan, Dan; Li, Jinyi; Chen, Siyu; Gu, Simeng; Jiang, Mingchen; Xu, Qiuyue (Frontiers in Neurology, 2025)
Sleep constitutes an essential physiological process that is vital for maintaining physical and mental wellbeing. However, the science of sleep focusing on basic questions such as “how” we sleep and “why” we sleep is still not clear. Over the past decade, substantial progress has also been made in elucidating the interactions between sleep and other biological processes, providing insights into the basic questions of sleep. Among these, emerging evidence highlights the microbiota-gut-brain axis (MGBA) as a pivotal bidirectional network that connects gut microorganisms with the central nervous system to regulate sleep architecture and homeostasis. This interaction is inherently bidirectional: sleep deprivation alters gut motility, mucosal integrity, and microbial composition, while microbial metabolites in turn influence neurotransmission (γ-aminobutyric acid, serotonin), immune-endocrine balance, and inflammatory signaling. In this article, we will review recent studies about MGBA-targeted therapeutic strategies for sleep disorders, such as probiotics, prebiotics, and fecal microbiota transplantation, which aim to restore microbial homeostasis and improve sleep quality. Furthermore, we discuss emerging interventions that modulate microbial metabolites and neuroimmune-endocrine signaling, as well as innovative pharmacological approaches targeting MGBA dysfunction. Collectively, we hope this review will contribute to a deeper understanding of MGBA-mediated mechanisms in sleep disorders promises to inform novel preventive and therapeutic strategies, ultimately improving clinical outcomes and quality of life for affected individuals.